159k views
1 vote
By using the completing the squares method solve
Xsquared-8x+3=0

2 Answers

5 votes

Answer:

x = 4 ±
√(13)

Explanation:

Given

x² - 8x + 3 = 0 ( subtract 3 from both sides )

x² - 8x = - 3

To complete the square

add ( half the coefficient of the x- term )² to both sides

x² + 2(- 4)x + 16 = - 3 + 16

(x - 4)² = 13 ( take the square root of both sides )

x - 4 = ±
√(13) ( add 4 to both sides )

x = 4 ±
√(13)

User Cwoebker
by
5.1k points
4 votes

Answer:

Explanation:

x^2 -8x +3 = 0

(x^2 - 8x + 16) = -3 + 16

(x-4)^2 = 13

x - 4 = (+/-)sqrt(13)

x = 4 +/- sqrt(13)

User Andreas Hunter
by
5.0k points